Fatigue in adults with congenital heart disease aged over 40 years - Linda Ternrud; Bengt Johansson; David Sparv; Zacharias Mandalenakis; Christina Christersson; Liesbet Van Bulck; Philip Moons; Camilla Sandberg; Joanna Hlebowicz (International Journal of Cardiology Congenital Heart Disease, 2025)
Structured abstract: Background: Fatigue is a symptom that has been described among adult patients with congenital heart disease (CHD), but the prevalence and impact of fatigue on the patient's daily life has been poorly studied. This study (i) examines the prevalence of fatigue in patients aged over 40 years with moderately complex or complex congenital heart disease compared to controls and (ii) explores the relationship between fatigue, heart disease complexity, clinical characteristics and self-reported New York Heart Association Functional Class (self-reported NYHA class). Methods: The Multidimensional Fatigue Inventory (MFI-20) was applied in 166 patients with moderately complex CHD or complex CHD (44 % females, median age 55.3 years, IQR 47.6–64.8) along with 89 controls (43 % female, median age 54.0, IQR 46.0–65.9). MFI-20 measured general fatigue, physical fatigue, mental fatigue, reduced motivation and reduced activity. Results: Physical fatigue (severe to very severe) was more common in complex CHD compared with moderately complex CHD (25 % vs. 52 %, p = 0.006). Complex CHD was associated with severe to very severe physical fatigue (odds ratio 3.1 (95 % CI 1.1–9.1). Patients with complex CHD had higher levels of self-reported NYHA class than patients with moderately complex CHD. All dimensions of fatigue were positively associated with self-reported NYHA class. Conclusions: Patients over the age of 40 with complex CHD were three times more likely to report severe to very severe physical fatigue and reported higher levels of self-reported NYHA class than patients with moderately complex CHD. This highlights the importance of considering CHD complexity in clinical practice.